Pengembangan Potensi Edu Wisata Lontar Sewu Melalui Media Sosial Tiktok - Putri, Fernanda Clarissa; Muhammad Danu Winata, S.Sos., M.A., M.Si (Han). (Universitas Negeri Surabaya, 2025)
This research aims to develop the potential of Lontar Sewu Tourism Education through the use of TikTok social media as a promotional and educational platform. Lontar Sewu, known for its natural beauty and cultural richness, has great potential to attract visitors, especially the younger generation. The research method used is a qualitative approach with data collection techniques through interviews, observation and analysis of TikTok content. The research results show that using TikTok can significantly increase Lontar Sewu's visibility. Creative content that displays natural beauty, educational activities and local culture can attract users' attention and increase interest in visits. In addition, the interactions that occur on this platform allow for more effective and participatory promotions. Recommendations from this research include developing an engaging content strategy and collaborating with local influencers to expand promotional reach. Thus, developing the potential of Lontar Sewu Tourism Edu through TikTok can not only increase the number of visitors but also enrich the tourist experience with relevant educational information.